Tai chi improves balance performance in healthy older adults: a systematic review and meta-analysis - Cui, Zhibo; Xiong, Jin; Li, Zhihua; Yang, Chengbo (Frontiers in Public Health, 2024)
BackgroundPrevious research has indicated that tai chi exercise can effectively enhance balance performance in patients; however, its impact on healthy individuals remains uncertain. Therefore, this meta-analysis aims to investigate the effects of different intensities and styles of tai chi exercise on the balance performance of healthy older adult individuals.MethodsA targeted search method was employed to identify studies investigating the impact of tai chi exercise on balance in older adults across a range of databases, including Web of Science, PubMed, Cochrane Central, EBSCO, CHKI, and Embase. The studies were conducted in accordance with the PRISMA and PERSiST guidelines, and two independent reviewers were responsible for the search, screening of results, extraction of data, and assessment of study quality. A random-effects model was employed to calculate the weighted mean difference (WMD) and 95% confidence interval (CI).Results2000 participants who met inclusion criteria were included in analyses across 28 trials. The findings indicated that tai chi can enhance the balance performance of healthy older adults, as demonstrated by the Timed Up and Go test (WMD = −1.04, 95% CI: −1.36 to-0.72, p < 0.00001, I2 = 71%), functional Reach test (FR) (WMD = 2.81, 95% CI: 1.60 to 4.02, p < 0.00001, I2 = 56%), and Berg Balance Scale (WMD = 2.55, 95% CI: 1.19 to 3.91, p = 0.0002, I2 = 88%), as well as other balance tests such as SLS (WMD = 5.03, 95% CI: 3.08 to 6.97, p < 0.00001, I2 = 85), and GS (WMD = 0.09, 95% CI: 0.05 to 0.12, p < 0.00001, I2 = 54%). Subgroup analyses showed that tai chi exercise for both ≤12 and > 12 weeks was statistically significant (< 0.01, respectively) for balance performance in healthy older adults, especially for tai chi exercise performed more than twice a week (WMD = −1.03, 95% CI: −1.35 to −0.72, p < 0.00001) and for more than 45 min each time (WMD = −1.11, 95% CI: −1.58 to-0.63, p < 0.00001) tai chi exercise had greater benefits on TUG time, FR distance and BBS in healthy older adults. In addition, compared to Sun-style tai chi, Yang-style tai chi was more effective.ConclusionThe tai chi exercise positively affects the balance performances of healthy older adults. Engaging in short-term (≤12 weeks) exercise for more than two 45-min sessions per week has been found to produce more pronounced effects. The effectiveness of Yang-style tai chi is superior to that of Sun-style tai chi.Systematic review registrationPROSPERO ID is CRD42024532577 https://www.crd.york.ac.uk/prospero/.